Mitochondrial genetic stability of Echinococcus granulosus s.s. across life stages and hosts in an experimental infection model - Celik, Figen; Uslug, Muhammet; Simsek, Sami (Elsevier, 2025)
Cystic echinococcosis, caused by Echinococcus granulosus sensu stricto (G1/G3), is a major zoonosis with a complex transmission cycle. This study aimed to evaluate the mitochondrial genetic stability of E. granulosus s.s. across different life stages and host species using a controlled experimental infection model. To achieve this, mitochondrial genetic variation was analyzed separately in protoscoleces (naturally infected sheep), adult worms (experimentally infected dogs), and hydatid cysts (experimentally infected lambs), to assess within- and betweengroup genetic stability. Mitochondrial gene regions CO1 (875 bp) and NADH1 (1009 bp) were amplified and sequenced. Phylogenetic, haplotype, and neutrality analyses revealed that all isolates clustered within a single monophyletic group. While CO1 showed moderate haplotype (Hd = 0.730) and low nucleotide diversity (pi = 0.00267), NADH1 displayed higher haplotypic and nucleotide diversity (Hd = 0.983; pi = 0.00876). Significantly negative Fu's Fs values for both markers suggested a recent demographic expansion, potentially driven by clonal amplification under low evolutionary pressure. Despite the presence of several haplotypes, no host- or tissuespecific genetic differentiation was observed. These findings demonstrate the genetic continuity of E. granulosus s.s. throughout its life cycle and confirm the suitability of mitochondrial markers for molecular tracking and epidemiological studies in endemic regions.
Keywords: Cystic echinococcosis; Echinococcus granulosus sensu stricto; CO1; NADH1; Mitochondrial diversity; Haplotype analysis